Measurement and Evaluation of Tx/ Rx Antennas for X-Band Radar System - Folin Oktafiani; Yuyu Wahyu; Yusuf Nur Wijayanto (Universitas Ahmad Dahlan, 2016)
This paper presents the performance evaluation of antennas for microwave transmission and reception in X-band radar systems. The transmitter (Tx) and receiver (Rx) antennas are fabricated on microstrip array structures. The antennas are connected to microwave circuits with transmission lines, coaxial cables, and microwave combiners and splitters. The designed antennas in X-band microwave operation for Tx and Rx parts were fabricated identically by 4x64 microstrip patch antennasin an array structure. The fabricated antennas were measured for return loss (S11), VSWR, radiation pattern, and Gain. The detail methods for the measurements are reported and their results are also discussed. The measured antenna gain of 20dBi, and beam-width of 20degreecan be obtained using the fabricated antennas at 9.4GHz microwave operation.